Presidential Permit to Summon Suspect of Corruption of the Member of the House of Representatives - Ramiyanto Ramiyanto (Faculty of Law, Sriwijaya University, Indonesia, 2018)
Summoning the suspect is one step in the process of investigation in the criminal justice system which had been regulated in the Criminal Code Procedure and in other special laws. However, presenting the suspect of the member of the Parliament before the Court is the problematic one. This is because in reality, it does not need a President permit but legally it does. The problem is whether pre-senting the suspect before the court without a Presidential Permit is not against the law. The findings showed that the regulation dealing with the summoning of the parliament member suspected of cor-ruption is not necessarily required. It is because the crime suspected to the members of House of Rep-resentative is included in the special crime which is stipulated the 2002 Law Number 30 deals with Corruption Eradication Commission Article 46 paragraph (1) with the elucidation in junction to Arti-cle 245 paragraph (3) sub paragraph c.